PEMBELAJARAN MULTIMEDIA IPA DENGAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Servitri, Margaretha Ordo (Universitas Pendidikan Indonesia, 2017)
The low learning achievement in science subjects especially about finding alternative energy sources is shown with the average grade grade 62,50 while the value of KKM 75 so that experimental learning through multimedia IPA with CTL model makes learning becomes interesting and meaningful for students. With details of two classes for field test. 24 students as treatment class that is class of VA SDN and 22 students as control class in VB SDN Wiyung 1 Surabaya. This experimental study was conducted to measure the effect before treatment was given (multimedia IPA with CTL) and after being given IPA multimedia treatment with CTL. Sheet of research instrument used in the form of interview sheet and questionnaire of student response to multimedia IPA as well as test sheet to measure learning result. The results show that the post-test average is higher than the average pre-test. Means multimedia with CTL in learning to give effect on the results of learning IPA magnitude increase occurred based on the calculation is 12.25%.Keywords: contextual teaching learning, multimedia, science education.